Intervensi Konseling Keluarga pada Dampak Pernikahan Jarak Jauh Terhadap Kesejahteran Psikologis Keluarga - Sona, Dwi; Wahyu Irawan, Andi (Jurnal Bimbingan dan Konseling Borneo, 2024)
families involved, affecting the dynamics and overall psychological well-being of the family. This study aims to evaluate the effectiveness of family counseling interventions in addressing the negative impacts faced by families with members in a long-distance marriage. The research incorporates both quantitative and qualitative methodological approaches to gather comprehensive data. Through surveys and in-depth interviews, the study involved 10 families experiencing long-distance marriages in Indonesia. The counseling interventions provided focused on enhancing communication skills, stress management, and strengthening family relationships during a three-month intervention period. The results indicate that the intervention successfully improved the psychological well-being of the families significantly. There was a noticeable improvement in the quality of communication, emotional understanding, and satisfaction within family relationships. Further analysis revealed that the effectiveness of the intervention was influenced by several factors, including the frequency of communication among family members, willingness to change, and the level of conflict prior to the intervention. The study concludes that family counseling intervention is a vital approach in supporting families to cope with the challenges posed by long-distance marriages. These findings provide important implications for counseling practices, the development of family intervention programs, and policies supporting family welfare